MANAJEMEN PONDOK PESANTREN DALAM MENGEMBANGKAN KOMPETENSI PROFESIONAL GURU DI PONDOK PESANTREN TERPADU ISTIQAMAH SIMAWANG - Muhamad Akmal (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
This research is aimed to know deeply about how (1) implementation of planning of muslim boarding school in development of teachers’ professional competence. (2) implementation of organizing of muslim boarding school in development of teachers’ professional competence.(3) actuating of muslim boarding school in development of teachers’ professional competence. (4) implementation of controling and evaluating of muslim boarding school in development of teachers’ professional competence at intergraited muslim boarding school of Istiqamah Simawang Batusangkar. This resarch is conducted by using qualitative research. It is an effert to get description about implementation of management of muslim boarding school in development of teachers’ professional competence at intergraited muslim boarding school of Istiqamah Simawang Batusangkar. The technigue of data collection is gotten based on observation by using interaction model, where the data is obtained, reducted, and displayed and drawing conclusion.Key Words: Manajemen, Pondok pesantren, kompetensi profesional